2008
DOI: 10.1111/j.1365-2141.2007.06956.x
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of ZHX2, but not RCBTB2 or RAN, is associated with poor outcome in multiple myeloma

Abstract: SummaryRAN, ZHX2 and RCBTB2 (CHC1L) expression was evaluated by quantitative real time reverse transcription polymerase chain reaction in plasma cells from 85 monoclonal gammopathies: 58 symptomatic multiple myeloma (MM) (52 untreated, six relapsed), eight smouldering MM, five monoclonal gammopathy of undetermined significance, four plasma cell leukaemias and 10 myeloid cell lines. ZHX2 was weakly expressed in high-risk/ proliferative disease compared to low-risk or indolent disease. High ZHX2 expression was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 13 publications
4
35
0
Order By: Relevance
“…In HL HLXB9 and HOXB9 have been identified as downstream targets of aberrant PI3K-and ERK5-signaling, respectively (Nagel et al, 2005(Nagel et al, , 2007. Expression of homeobox gene ZHX2 is deregulated in MM and DLBCL (Harousseau et al, 2004;Hystad et al, 2007;Armellini et al, 2008), however, the mechanisms of deregulation and its pathologic function remained unknown. In MM low expression levels of ZHX2 are associated with poor prognosis, indicating tumor suppressor activity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In HL HLXB9 and HOXB9 have been identified as downstream targets of aberrant PI3K-and ERK5-signaling, respectively (Nagel et al, 2005(Nagel et al, , 2007. Expression of homeobox gene ZHX2 is deregulated in MM and DLBCL (Harousseau et al, 2004;Hystad et al, 2007;Armellini et al, 2008), however, the mechanisms of deregulation and its pathologic function remained unknown. In MM low expression levels of ZHX2 are associated with poor prognosis, indicating tumor suppressor activity.…”
Section: Discussionmentioning
confidence: 98%
“…Deregulated expression has been described in MM and DLBCL. Moreover, in MM low ZHX2 levels have been connected with poor prognosis, indicating tumor suppressor activity in this B-cell malignancy (Harousseau et al, 2004;Armellini et al, 2008;Hystad et al, 2007).…”
Section: Breakpoint At 8q24 Targets Homeobox Gene Zhx2mentioning
confidence: 99%
“…Shaughnessy et al 33 found that low expression of ZHX2 was associated with a risk of progression in a selected series of 221 transplanted patients with MM. In addition, lower expression of ZHX2 protein was detected in high-risk proliferative MM than in low-risk proliferative MM, 34 and the expression level of ZHX2 protein was closely related with the invasion ability of MM. 35 Some properties of ZHX2 are taken into an important prognostic marker for MM.…”
Section: Hematological Diseasesmentioning
confidence: 96%
“…The increased ZHX2 mRNA level was associated with beneficial prognostic index like β 2 -microglobulin o 5.5 mg l − 1 , albumin 435 g l − 1 or a better cytogenetics. 34 Furthermore, high expression level of ZHX2 correlated with prolonged duration of response and overall survival of patients. 34 In addition, the patients with low ZHX2 levels had a higher rate of resistance to chemotherapy.…”
Section: Hematological Diseasesmentioning
confidence: 99%
See 1 more Smart Citation